MOTIVATION OF THE PROFESSIONAL DEVELOPMENT OF TEACHERS DURING THE WAR IN UKRAINE - Олексенко, Світлана; Хоменко, Олена (SWorldJournal, 2024)
The article highlights the results of research into the motives of professional development of teachers during the war period in Ukraine. Also, stimulating and hindering factors of professional development, currently relevant directions for professional i